In Vitro Micropropagation of Industrially and Medicinally Useful Plant Aloe trichosantha Berger Using Offshoot Cuttings - Atsbeha Hailu; Desta Berhe Sbhatu; Haftom Baraki Abraha (The Scientific World Journal)
This study was aimed to develop in vitro micropropagation protocol of Aloe trichosantha Berger using offshoots as explants. MS media supplemented with plant growth regulators helped explants develop shoots within about 14 to 17 days. The mean number of days to shooting has decreased from 16.8 ± 0.8 with 0.5/0.5 mg/L BAP/NAA supplement to 15.5 ± 0.5 with 2.0/0.5 mg/L BAP/NAA. While the mean shoot number has increased with increasing the concentration of BAP supplements, the reverse was true with mean shoot lengths, whereas supplement of 2.0/0.5 mg/L BAP/NAA has generated significantly more shoots (17 ± 3.8), and longer shoots were produced with the addition of 0.5/0.5 and 1.0/0.5 mg/L BAP/NAA. In regard to rooting, though higher concentrations of NAA have resulted in quick rooting, the rooting performance in terms of mean number and length of roots was better with low concentrations. All the plantlets subjected to greenhouse acclimatization in cocopeat have survived. Secondary acclimatization in composted and manured soil media has also resulted in 93 to 95% survival rate. Lighting conditions (nursery shade or direct sunlight) of secondary acclimatization did not lead to any difference in the survival rate of the plantlets.